2013
DOI: 10.3354/esr00523
|View full text |Cite
|
Sign up to set email alerts
|

Displacement responses of a mysticete, an adontocete, and a phacid seal to construction-related vessel traffic

Abstract: Marine construction works often lead to temporary increases in vessel traffic, which, in addition to the construction activity itself, contribute to underwater ambient noise in the affected area and increase the risk of vessel collision for marine mammals. Using a 3 yr data set of cliff-based observations, we investigated whether the presence/absence of minke whales, bottlenose dolphins and grey seals varied with the overall number and type of vessels present during the construction of an underwater gas pipeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Behavior of cetaceans was classified into four categories: (i) traveling-normally moving animals on a steady course, (ii) resting-stationary in one place, almost without movement, (iii) socializing-clear and constant interaction between the animals in a normally stationary group, and (iv) foraging-non−synchronized movements and very active animals, normally involving the visualization of prey or aggregation of birds (Alves et al, 2018). We added (v) "bow riding" as a special category, since the behavior is prevalent in small cetaceans, and it shows a cue of being attracted to vessels (Anderwald et al, 2013).…”
Section: Additional Important Informationmentioning
confidence: 99%
“…Behavior of cetaceans was classified into four categories: (i) traveling-normally moving animals on a steady course, (ii) resting-stationary in one place, almost without movement, (iii) socializing-clear and constant interaction between the animals in a normally stationary group, and (iv) foraging-non−synchronized movements and very active animals, normally involving the visualization of prey or aggregation of birds (Alves et al, 2018). We added (v) "bow riding" as a special category, since the behavior is prevalent in small cetaceans, and it shows a cue of being attracted to vessels (Anderwald et al, 2013).…”
Section: Additional Important Informationmentioning
confidence: 99%
“…When considering the upper limits of the 95% confidence intervals, these predicted values exceeded the estimated thresholds for the onset of TTS (Southall et al, 2007(Southall et al, , 2019. Locally in Broadhaven Bay, Ireland, gray seals potentially varied habitat use in response to vessels as indicated by a negative correlation between the numbers of gray seals and construction vessels (Anderwald et al, 2013). A recent study using acoustic tags (DTAGs) that record sound and behavior concurrently showed that harbor and gray seals were exposed to vessel noise 2.2-20.5% of their time at sea (Mikkelsen et al, 2019).…”
Section: Pinnipedsmentioning
confidence: 86%
“…Cliff-based surveys have shown that seals are less likely to be sighted when vessel traffic is high (Anderwald et al, 2013). Our study had insufficient data to determine firmly whether seals showed behavioural avoidance of shipping within the available tracking data.…”
mentioning
confidence: 86%